Analytical study of in-plane buckling of longitudinal bars in reinforced concrete columns under extreme earthquake loading. (1st March 2017) - Nojavan, Alireza; Schultz, Arturo E.; Chao, Shih-Ho
Highlights: Seven full-scale RC columns were tested under distinct lateral loading protocols. During the tests, longitudinal bars buckled parallel to the face of the column. Transverse ties showed little or no effect restraining in-plane bar buckling. 3D FEM analyses were conducted to better understand the phenomenon. Abstract: Seven full-scale reinforced concrete (RC) columns were tested at the Multi-Axial Subassemblage Testing (MAST) Laboratory of the University of Minnesota to investigate their performance under extreme seismic events. The specimens were designed according to seismic provisions of ACI 318 - 11 (ACI Committee 318, 2011) and incorporated closely-spaced transverse hoops at their base. However, at large drift ratios during these tests, longitudinal bars were observed to buckle parallel to the face of the columns with transverse ties having little effect. This previously unobserved bar buckling phenomenon is investigated numerically to gain a better understanding of the column characteristics that affect it. First, a bar-spring mechanical model is used to understand the conditions needed to prevent buckling of longitudinal bars by means of restraints with finite stiffness. Second, a three-dimensional (3D) nonlinear finite element analysis of the lower portion of the specimen subjected to monotonic loading was formulated in ABAQUS and validated with test data. The analysis reveals that columns with larger cross-sectional dimensions that incorporate larger longitudinal bar sizes (No. 8 and above) and lower strength concrete are more prone to in-plane bar buckling.